PENGARUH MEDIA MISTERY BOX TERHADAP PEMAHAMAN KONSEP IPAS SISWA KELAS IV UPT SPF SD INPRES BONTOMANAI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the understanding of fourth-grade students' science concepts at the UPT SPF SD Inpres Bontomanai in learning using the Mystery Box media. This study used a Quasi-Experimental Design method. The population in this study was all 66 fourth-grade students at the UPT SPF SD Inpres Bontomanai. The sampling technique used was total sampling or saturated sampling. The results showed that the level of understanding of science concepts in the experimental class using the Mystery Box media obtained an average score of 81.94, categorized as high, and achieved classical mastery of 87.9%. Meanwhile, in the control class not using the Mystery Box media, the average score was 65.15, categorized as moderate, and achieved classical mastery of 21.2%. The hypothesis test results obtained a significance value of 0.001 (0.001 < 0.05), thus H₀ was rejected and H₁ was accepted. Based on these results, it can be concluded that there is a significant effect between learning using the Mystery Box media and learning without it on the understanding of fourth-grade students' science concepts at the SPF Unit of Bontomanai Elementary School.